Desgaste erosivo de revestimentos WC-Cr-Co depositados via processos de soldagem PTA-P e por manta sinterizada - Bragança, Bruno Corveto (2016)
This work studies the solid particle erosion behavior of WC-Co-Cr coatings, deposited by welding process PTAP (Plasma Transferred Arc Powder) and infiltration brazed. These materials are used for covering components subject to erosive wear, since they are hard phase coatings with ductile matrix. Tests were performed in the gas blast erosion test apparatusavailable in the Laboratory TRICORRMAT (Tribology, Corrosion and Materials) at UFES (Universidade Federal do Espírito Santo), in three different conditions. In the first condition, the particle was alumina, with an impact angle of 90° at hightemperatureof 375°C. For the second and third conditions studied, test were performed at room temperature with hematite as particle, and the variable evaluated was the angle of impact, consisting of 90 and 30. For all three conditions, the impact speed was 70 m/s and the flux rateof particles was 2 mg/mm².s. Tests were conducted to ASTM G 76.The wear mechanisms were investigated by MEV images. It’ll show that the microstructures originated by deposition process influenced wear rate directly. Besides that, the effects of temperature and particle hardness will be understood